PENGARUH PROMOSI & PELAYANAN ONLINE FOOD DELIVERY TERHADAP KEPUTUSAN PEMBELIAN DI TORE JAPANESE EATERY BATAM - Karrika Sari; Nuryanto, Heri (JURNAL MENATA, 2022)
In this digital era, online food delivery services make life easier not only for consumers but also for the culinary industry such as Tore Japanese Eatery Batam. But, Tore Japanese Eatery Batam is having a climbdown on online food delivery purchases these past 6 months. A lot of complaints about promotion and service are also popping up on the Instagram comment section at @gofoodindonesia and @grabfoodid. The purpose of this research is to analyze how sales promotion and service quality are giving impact on online food delivery purchase decisions at Tore Japanese Eatery Batam. This research also looks for the difference in sales promotion and service quality given by Gofood and Grabfood at Tore Japanese Eatery Batam. This is comparative and associative research using quantitative method with 212 people as the sample. Multiple linear regression and Mann-Whitney test were used as the data analyzing tools for this research. The research’s findings revealed that (1) There is no significant difference in sales promotion given between Gofood and Grabfood, (2) There is no significant difference in service quality given between Gofood and Grabfood, (3) Sales promotion is giving positive impact on purchase decision, (4) Service quality is giving positive impact on purchase decision, (5) Both sales promotion and service quality are giving positive impact on online food delivery’s purchase decision at Tore Japanese Eatery Batam.